This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution! +1
I have better one gentlman
let t=sqrt (x/2+13/16)
So the equation becom
2t^2-13/8-sqrt (t^2-1/2t+1/16)=179
2t^2-13/8-t+1/4=179
2t^2-t-11/8=179
2 ×(2t^2-t-11/8)/2=179
4t^2-2t+1/4-3=358
(2t-1/2)^2=361
t=9,75
Sqrt (x/2+13/16)=9,75
x=188,5
Am I genius ?
Log in to reply
Learn to put '.'
not genius more like autist, bad solution
Log in to reply
C'mon man, learn to be kind. He posted a good solution.
Log in to reply
@Saúl Huerta – Alt??? Wtf bro, no one would actually think that is good lOL
Need to add absolute value after removing radical at 3-4 line.
Note that ( 2 8 x + 6 4 1 3 − 4 1 ) 2 = 4 ( 8 x + 6 4 1 3 ) − 8 x + 6 4 1 3 + 1 6 1 = 2 x + 8 7 − 8 x + 6 4 1 3 .
It is clear x > 0 and 2 8 x + 6 4 1 3 > 2 6 4 1 3 > 4 1 and hence 2 x + 8 7 − 8 x + 6 4 1 3 = 2 8 x + 6 4 1 3 − 4 1 .
Now x − 2 x + 8 7 − 8 x + 6 4 1 3 = x − ( 2 8 x + 6 4 1 3 − 4 1 ) = x + 4 1 − 2 x + 1 6 1 3 .
Note that ( 2 2 x + 1 6 1 3 − 2 2 1 ) 2 = ( x + 8 1 3 ) − 2 x + 1 6 1 3 + 8 1 = ( x + 4 1 − 2 x + 1 6 1 3 ) + 2 3 .
Now x − 2 x + 8 7 − 8 x + 6 4 1 3 = ( 2 2 x + 1 6 1 3 − 2 2 1 ) 2 − 2 3 = 1 7 9
Hence, ( x + 8 1 3 − 2 2 1 ) 2 = 1 7 9 + 2 3 = 2 3 6 1 = ( 2 1 9 ) 2
Finally, solving it to obtain x = ( 2 1 9 + 2 2 1 ) 2 − 8 1 3 = 1 8 8 . 5 and hence 1 0 x = 1 8 8 5 .
Though the exact answer I got was 1884.9999. But yeah I got it.
Let u = 8 x + 6 4 1 3
⟹ 8 u 2 − 8 1 3 − 4 u 2 − 1 6 1 3 + 8 7 − u = 1 7 9
8 u 2 − 8 1 3 − 4 u 2 − u + 1 6 1 = 1 7 9
8 u 2 − 8 1 3 − ∣ ∣ ∣ ∣ 2 u − 4 1 ∣ ∣ ∣ ∣ = 1 7 9
Since x ≥ 1 7 9 ⟹ u ≥ 8 1 7 5 and 2 u > 4 1
⟹ 8 u 2 − 8 1 3 − ( 2 u − 4 1 ) = 1 7 9
8 u 2 − 2 u − 8 1 4 4 3 = 0
⟹ u = 8 3 9 = 8 x + 6 4 1 3
⟹ x = 2 3 7 7
∴ 1 0 x = 1 8 8 5
Problem Loading...
Note Loading...
Set Loading...